Avaliação de interações medicamentosas potenciais em prescrições para idosos com Síndrome Coronariana Aguda da cardiologia clínica de um hospital de ensino - Lima, Tiago Aparecido Maschio de (2016)
Introduction: Despite the need, it is verified the use of high number of drugs in patients affected by Acute Coronary Syndrome, causing problems related to drugs, among them, the drug interactions representing serious problems, resulting in severe adverse events or inefficacy of drug therapy. Objectives: The aim of this study was to investigate the prescriptions for elderly diagnosed with acute coronary syndrome hospitalized in the clinical cardiology unit of a teaching hospital and to determine the rate of theoretical potential drug interactions present in prescriptions. Methods: Descriptive exploratory study with analysis of 607 medical prescriptions throughout the period of hospitalization of 119 elderly patients 60 years or older in the period from April to July 2014. We collected demographic data from the patients, the information related to prescription drugs and the prescription indicators. The computerized databases Micromedex, Drugs and Medscape were used to identify the drug interactions that were classified according to their intensity level, mechanism and documentation. Results: The average age was 71 ± 8 and 55% were male. It was identified the quantitative of 7266 prescription drugs and the average of 12 ± 3 drugs per prescription, minimum of three and maximum of 23 prescription drugs. The most prescribed therapeutic classes were antiplatelets, anticoagulants, analgesics and antilipemics. Acetylsalicylic acid, Atorvastatin, dipyrone, and clopidogrel were the most prescribed drugs. The oral administration and the tablets were the most used. Only 74% were prescribed in accordance with the generic nomenclature, most obeyed the hospital standardization list, and there was a low frequency of antimicrobial and controlled drugs. 10162 interactions were detected and distributed among 554 types of different combinations of prescribed drugs and 99% of prescriptions presented at least one and maximum of 53 interactions, being highlighted the prevalence of moderate and major, 64% and 25%, respectively. There was a correlation between the number of interactions and the number of prescription drugs and hospitalization time. Conclusions: The high rate of interactions present in the prescriptions of patients with Acute Coronary Syndrome emphasizes the importance of clinical pharmacists activities for the identification and management of interactions, and monitoring of patients through critical analysis based on evidence, contributing to the necessary medical interventions and achieves better therapeutic results. The information gathering on the profile of prescription performed by clinical pharmacists in partnership with the multidisciplinary health team contributes to the analysis of clinical and scientific data, optimization of pharmacotherapy, the reduction of pharmacotherapeutic results unfavorable and pharmacoeconomics in the health system.